IL‐33 drives airway hyper‐responsiveness through IL‐13‐mediated mast cell: airway smooth muscle crosstalk. Issue 5 (16th March 2015) - Kaur, D.; Gomez, E.; Doe, C.; Berair, R.; Woodman, L.; Saunders, R.; Hollins, F.; Rose, F.R.; Amrani, Y.; May, R.; Kearley, J.; Humbles, A.; et al.
Abstract Background Mast cell localization within the airway smooth muscle (ASM)‐bundle plays an important role in the development of airway hyper‐responsiveness (AHR). Genomewide association studies implicate the 'alarmin' IL‐33 in asthma, but its role in mast cell–ASM interactions is unknown. Objectives We examined the expression and functional role of IL‐33 in bronchial biopsies of patients with and without asthma, ex vivo ASM, mast cells, cocultured cells and in a mouse model system. Methods IL‐33 protein expression was assessed in human bronchial tissue from 9 healthy controls, and 18 mild‐to‐moderate and 12 severe asthmatic patients by immunohistochemistry. IL‐33 and ST2 mRNA and protein expression in human‐derived ASM, epithelial and mast cells were assessed by qPCR, immunofluorescence and/or flow cytometry and ELISA. Functional assays were used to assess calcium signalling, wound repair, proliferation, apoptosis and contraction. AHR and inflammation were assessed in a mouse model. Results Bronchial epithelium and ASM expressed IL‐33 with the latter in asthma correlating with AHR. ASM and mast cells expressed intracellular IL‐33 and ST2. IL‐33 stimulated mast cell IL‐13 and histamine secretion independent of FcεR1 cross‐linking and directly promoted ASM wound repair. Coculture of mast cells with ASM activated by IL‐33 increased agonist‐induced ASM contraction, and in vivo IL‐33 induced AHR in a mouse cytokine installation model; both effects were IL‐13 dependent. Conclusion IL‐33 directly promotes mast cell activation and ASM wound repair but indirectly promotes ASM contraction via upregulation of mast cell‐derived IL‐13. This suggests that IL‐33 may present an important target to modulate mast cell–ASM crosstalk in asthma.